2016
DOI: 10.1177/0961203316659546
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between health-related quality of life, disease activity and disease damage in a prospective international multicenter cohort of childhood onset systemic lupus erythematosus patients

Abstract: Previously, we described associations between health-related quality of life (HRQOL) and disease-related factors among childhood onset systemic lupus erythematosus (cSLE) patients. Here we determined the relationship between HRQOL, disease activity and damage in a large prospective international cohort of cSLE. We compared HRQOL, disease activity and disease damage across different continents and examined the relationship between children's and parents' assessments of HRQOL. Patients with cSLE and their parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
(43 reference statements)
2
37
0
Order By: Relevance
“…High disease activity (SLEDAI‐2K ≥8) had a significant negative effect on HRQoL, which is supported by other studies . Interestingly, an even larger negative effect was seen with regard to factors affecting physical appearance.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…High disease activity (SLEDAI‐2K ≥8) had a significant negative effect on HRQoL, which is supported by other studies . Interestingly, an even larger negative effect was seen with regard to factors affecting physical appearance.…”
Section: Discussionsupporting
confidence: 80%
“…In children with childhood‐onset SLE, health‐related quality of life (HRQoL) has been shown to be impaired compared to healthy peers, which has been at least partially attributed to disease activity and damage . There were no data available regarding HRQoL in adult patients with childhood‐onset SLE or pertaining to the specific factors that could influence HRQoL in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moorthy et al. () conducted a longitudinal study on the relationship between health‐related quality of life and the disease parameters of SLEc. The findings indicated that disease activity and disease damage were not significantly different across the time continents throughout the 3‐year period.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective international multicenter longitudinal cohort study (n=467) found that higher disease activity and higher damage was associated with lower HRQoL in cSLE patients 29 . On the other hand in our study, and in line with some earlier studies, disease activity and accumulated damage were not found to highly correlate with HRQoL in cSLE 5, 6 .…”
Section: Discussionmentioning
confidence: 99%